Salvaged - Collins, Nicolas 1954- (Chicago Trace Elements Records, 2015)
The works on this DVD reflect my recent interest in complexity and chaos - a byproduct of workshops I've been presenting for the past decade, in which I often find myself in a sonic landscape of 25 small speakers blaring the experiments of 25 novice hackers. My music has always been intended for live performance and from the time I made my first record I've been aware of how much is lost when that experience is recast as a purely audio document, bereft of visual content. The DVD format makes it possible to deliver a visual component (albeit reduced) and to replicate the multi-channel audio experience of the performances through Dolby 5.1.Tall Poppies was originally a three-channel video installation in the Diapason Gallery in Brooklyn. Contact mikes on the stems of sparklers pick up the whoosh of the burning magnesium and the subsequent ping and pop of the wire cores as they cool (these sounds are not processed in any way). Video projectors beam synchronized recorded loops of individual sparklers onto the walls of the gallery, each image accompanied by its own sound channel. This DVD reformats the video into a single widescreen image, with three channels of audio arrayed in the 5.1 field.The Royal Touch and Salvage reanimate deceased, discarded electronic circuitry (cell phones, computer motherboards, etc.) The performers make connections between simple circuits of my design and the electronic corpses; feedback between my circuit and the components on the dead boards produces complex patterns of oscillation that change in response to the slightest movement of the contact points. In The Royal Touch a solo performer makes these connections through fishing weights. In Salvage six players manipulate test probes, occasionally suspending their activity when signaled to do so by a seventh player with a light cue.Waggle Dance, for laptop marching band, was written for the Princeton Laptop Orchestra (PLOrk). The sound material consists of feedback between the internal mikes and speakers in the laptops, triggered by crackle noise extracted from antique cylinder recordings. The screens light the performers' faces as they wander in the dark.In Imperfekt the sounds of a barely-functional Soviet radio pass through a maze of computer signal processing.In Memoriam Michel Waisvisz employs a candle's flicker to control the tuning of four oscillators.Tobabo Fonio, an older piece, is a live reworking of brass band music from the Peruvian Andes. The sounds are transformed by a digital signal processor controlled by, and playing back through, an old trombone. The initial samples are so short they are heard as drones, sprayed around the room by the highly directional trombone speaker. The pitch deepens as the samples are lengthened, gradually giving way to bursts of trumpet riffs and drum rolls, and finally brief glimpses of the Cusqueña music at its core.DVD production and mastering by Austen Brown at the School of the Art Institute of Chicago, 2015.This disc is also included in the book Nicolas Collins: Micro Analyses. Van Dieren Éditeur, Collection Rip on/off, Paris, 2015
Keywords: 21st Century (2001-2100); Artistic research